2020
DOI: 10.24106/kefdergi.4075
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Instructional Process Carried out by the Science Teachers with Mainstreaming Students Diagnosed Learning Disabilities

Abstract: Bu çalışmanın amacı; fen bilimleri öğretmenlerinin öğrenme güçlüğü tanılı kaynaştırma öğrencileri ile yürüttükleri öğretim sürecinin incelenmesidir. Bu çalışma betimsel bir araştırma niteliğindedir. Çalışma Milli Eğitim Bakanlığı'na bağlı okullarda görev yapan 121 fen bilimleri öğretmeni ile yürütülmüştür. Veri toplama aracı olarak; anket ve mülakat kullanılmıştır. Anket 121 fen bilimleri öğretmenine uygulanmıştır. Anketlerden elde edilen bulgular doğrultusunda daha derinlemesine bilgi elde edebilmek amacıyla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…It has been determined that students' active participation in the lesson makes them happy and is beneficial for the students. Similarly, in some studies, science teachers stated that most mentally disabled students were able to use more observation skills (Dilber, 2017;Er Nas et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It has been determined that students' active participation in the lesson makes them happy and is beneficial for the students. Similarly, in some studies, science teachers stated that most mentally disabled students were able to use more observation skills (Dilber, 2017;Er Nas et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The findings indicated that that the prospective teachers completely agreed with the statements in F4 (Interaction with plants), but also positively agreed with the statements in other factors. One of the reasons why students have trouble trying to learn science concepts is that they cannot relate science concepts to daily life (Er Nas et al, 2018;Stolk et al, 2012). Biology, an important field of science, is also a branch of science intertwined with daily life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Araştırmanın güvenirlik çalışmaları kapsamında kodlayıcılar arası güvenirlik düzeyi hesaplanmıştır. Nitel araştırmalarda kodlayıcılar arası güvenirliğin %90 güven aralığında olması beklenmektedir (Miles ve Huberman, 2015). Buna istinaden elde edilen veriler doğrultusunda "Güvenirlik=Görüş Birliği/(Toplam Görüş Birliği+Toplam Görüş Ayrılığı)" formülüyle yapılan hesaplamada %92 düzeyinde uzlaşı elde edilmiştir.…”
Section: Geçerlik Ve Güvenirlikunclassified